ANALISIS PERDAGANGAN INDONESIA PASCA PEMBERLAKUAN ACFTA (STUDI KOMPARATIF INDONESIA-CHINA) - . Muslihati (Jurnal Ekonomi Pembangunan, 2010)
Every international economy linking countries through two channels: trade in goods and services (real sector) and financial sector. Trade relations means that some products from a country that exported abroad, while some goods that are consumed or invested in the country are imported from abroad. The strong role of international trade is partly reflected in the goods market will be able to help us to know how big contribution to the real sector is affected by exchange rate and net exports to increase income or national output. All economies, regardless of size, depends on other economies and are affected by events beyond its limits.The existence of an agreement between Indonesia and China as stipulated in the agreement more or less ACFTA will influence the increase or decrease in Indonesia's trade balance are reflected in an increase or decrease in GNP. Indonesia's ability to see its comparative advantage will be able to increase the competitiveness of Indonesian products in the international market.